The electromechanical response of polymer networks with long-chain molecules. (July 2015) - Cohen, Noy; deBotton, Gal
The coupled electromechanical response of a polymer with long chains is analyzed in terms of the local response and distribution of the dipolar monomers. A comparison between two variational statements for a continuous and a discrete system leads to an estimate for the coupled electromechanical energy-density function of the polymer. Two types of dipolar monomer are considered, and the variations in the macroscopic responses of polymers with random distributions of chains are determined. Lastly, the analytical predications are favorably compared with recent experimental measurements.